Synthesis, characterization, and performance evaluation of polymeric hindered amine light stabilizers (HALS) in EPDM - Rana, Sravendra; Singh, Raj Pal (E-Polymers, 2007)
Polymeric hindered amine light stabilizer (HALS), wherein the hindered amine functionality was attached to the brominated ethylene-propylene-diene terpolymer (EPDM) was synthesized. The brominated EPDM was synthesized as an intermediate for the synthesis of a new polymeric hindered amine light stabilizer. The grafting and functionalization reactions were characterized by FTIR and (HNMR)-H-1 spectroscopy. The photostabilizing efficiency of this polymeric HALS was studied and compared with conventional HALS under accelerated weathering conditions. The results of the study give evidence for superiority of polymeric HALS over that of melt blended conventional HALS.
Keywords: EPDM; Photostabilization; polymeric HALS

Synthesis and drug-delivery behavior of chitosan-functionalized graphene oxide hybrid nanosheets - Rana, Vijay Kumar; Choi, Myeon-Cheon; Kong, Jin-Yeon; Kim, Gwang Yeon; Kim, Mi Ju; Kim, Sun-Hee; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Macromolecular Materials and Engineering, 2011)
Chitosan-functionalized graphene oxides (FGOCs) were successfully synthesized. FGOCs were found to significantly improve the solubility of the GO in aqueous acidic media. The presence of organic groups was confirmed by means of XPS and TGA. Restoration of the sp(2) carbon network and exfoliation of graphene sheets were confirmed by Raman spectroscopy, UV-visible spectroscopy and WAXD. The SEM and AFM investigations of the resultant FGOCs showed that most of the graphene sheets were individual and few were layered. Controlled release behavior of Ibuprofen and 5-fluorouracil was then investigated. We found that FGOCs are a promising new material for biological and medical applications.
Keywords: Biocompatibility; Chitosan; drug delivery systems; functionalization of polymers; solution properties

Stabilization of γ-sterilized low-density polyethylene by synergistic mixtures of food-contact approval stabilizers - Alariqi, Sameh A. S.; Al-Areqi, Niyazi A. S.; Alaghbari, Elyas Sadeq; Singh, Raj Pal (International Journal of Industrial Chemistry, 2017)
In our previous studies, we have found the synergistic combinations of stabilizers which follow different mechanisms of stabilization and are approved for food contact applications. The present attempt is to test the potentials of those systems in stabilizing γ-sterilized low-density polyethylene (LDPE). The results were discussed by comparing the stabilizing efficiency of mixtures with and without phenol systems as well as with their counterparts of isotactic polypropylene (iPP) and ethylene-propylene copolymers (EP) matrices. LDPE has been melt-mixed with tertiary hindered amine stabilizer (tert-HAS), oligomeric HAS stabilizer, phenolic and organo-phosphite antioxidants and subjected to γ-sterilization. Stabilization in terms of changes in oxidation products, tensile properties, yellowing and surface morphology was evaluated by FT-IR spectroscopy, Instron, colorimetry, and scanning electron microscopy (SEM), respectively. The results of the present study confirm the validity of those systems for protecting various polyolefins against γ-sterilization. The results showed that the synergism, antagonism and the trend in stabilization efficiency of the binary, ternary and quaternary stabilizer systems were almost similar in LDPE, iPP and EP matrices. The binary system of oligomeric HAS and tert-HAS has shown the antagonistic effect of stabilization, whereas their combination with organo-phosphite has exhibited synergistic effect even at higher doses of γ-sterilization. The combination of oligomeric HAS, tert-HAS, organo-phosphite and hindered phenol exhibited improved stabilization efficiency than single or binary additive systems. The phenol systems have shown long term of stability than that of phenol-free systems. It was found that the consumption of oligomeric stabilizer significantly depends on the components of stabilization mixture. It was concluded that the stability of polyolefins (LDPE, iPP and EP) against γ-sterilization can be achieved by blends of different stabilizers which are approved for food contact applications.